Prevalence and Correlation of Vitamin B12 and Vitamin D Levels Among Jordanian Patients - Eman N. Alfrehat; Essra M. Alnsour; Enas M. Al Hmeisat; Firas Alsoleihat (European Scientific Journal, ESJ, 2024)
Introduction: Essential nutrients for many physiological processes, such as bone integrity and neurological functioning, include vitamin D and B12. Notwithstanding their significance, deficits in these vitamins are common and can result in serious health issues. The purpose of this study is to evaluate the vitamin B12 and vitamin D levels in a representative sample of Jordanians who were referred to the Royal Medical Services' King Hussein Medical Center, a major referral medical center in the capital city of Jordan, Amman. Methods: For this study, a total of 70 participants-45 girls and 25 males-were randomly chosen. Vitamin B12 and Vitamin D levels were determined by analyzing blood samples and gathering data from normal medical checkups. To compare levels and insufficiency rates between sexes, descriptive statistics were calculated and independent samples t-tests and chi-square tests were used. To investigate the correlations between age, vitamin B12, and vitamin D levels, Pearson correlation coefficients were computed. Results: The mean levels of vitamin B12 and vitamin D in females were 388.10 pg/mL and 21.40 ng/mL, respectively. The mean levels of vitamin B12 and vitamin D in males were 429.91 pg/mL and 25.44 ng/mL, respectively. There were no discernible variations in vitamin B12 and vitamin D levels between the sexes (p > 0.05). On the other hand, males (9.5%) had considerably greater levels of vitamin B12 deficiency than females (0.0%) (p = 0.036). Males' vitamin B12 and vitamin D levels showed a significant positive correlation (r = 0.448, p = 0.042) as did the pooled sample (r = 0.316, p = 0.020). Conclusion: The study shows that there is a significant positive correlation between vitamin B12 and vitamin D levels and that male participants were more likely to be insufficient in vitamin B12. In order to address and prevent these deficits in the Jordanian population, these findings highlight the necessity of focused dietary interventions and public health initiatives.